Reevaluation and Reorientation of the Philosophy of Retributive Justice to Restorative Justice in Imposing Criminal Sanctions - Padlilah Padlilah; Dey Ravena; Chepi Ali Firman Zakaria; Aji Mulyana (Borong Newinera Publisher, 2023)
In the last few decades, there has been a paradigm shift in the provision of criminal sanctions from retributive justice to restorative justice. Retributive justice assumes that criminal punishment must be based on the concept of revenge and retribution for the mistakes made by the perpetrator, while restorative justice emphasizes recovery for the victim and repairing the damaged relationship between the perpetrator and the victim. This study discusses the re-evaluation and reorientation of the philosophy of retributive justice to restorative justice in imposing criminal sanctions, as well as the purpose of punishment itself. This article presents the history and basic concepts of both types of justice, as well as the advantages and disadvantages of each approach. In addition, this research also discusses the application of restorative justice in sentencing practices and how this approach can help improve the relationship between perpetrators and victims, as well as prevent crimes from occurring in the future. By examining and considering both approaches, this research can help improve the existing penal system to achieve goals that are more effective and fairer for all parties involved in the sentencing process.